Long-Term Results up to 12 Months After Catheter-Based Alcohol-Mediated Renal Denervation for Treatment of Resistant Hypertension. (2nd September 2021) - Mahfoud, Felix; Sievert, Horst; Bertog, Stefan; Lauder, Lucas; Ewen, Sebastian; Lengelé, Jean-Philippe; Wojakowski, Wojciech; Schmieder, Roland; van der Giet, Markus; Weber, Michael A.; Kandzari, David E.; Parise, Helen; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Primary results of this prospective, open-label, multicenter trial suggested that alcohol-mediated renal denervation with perivascular injection of dehydrated alcohol using the Peregrine System Infusion Catheter safely reduces blood pressure (BP) in patients with resistant hypertension. To date, maintenance of the BP-lowering effect beyond 6 months using this novel technology has not been reported. This article describes the final, 12-month follow-up data on the safety and efficacy of alcohol-mediated renal denervation in these patients. Methods: Forty-five patients with resistant hypertension on a stable regimen of on average 5.1±1.5 antihypertensive medications underwent successful bilateral renal denervation using the Peregrine Catheter with alcohol as the neurolytic agent (0.6 mL per renal artery). Apart from 2 vascular access pseudoaneurysms (both without sequelae), no major procedural complications occurred. Results: At 12 months post-procedure, mean 24-hour ambulatory systolic and diastolic BP were reduced by 10 mm Hg (95% CI, −16 to −5) and 7 mm Hg (−10 to −3), respectively ( P <0.001). Office systolic/diastolic BP was reduced by 20/10 mm Hg (−27, −13/−14, −6; <0.001). Compared with baseline, the number of antihypertensive medications was reduced in 21% of patients, while it was increased in 19%. From baseline to 12 months, serum creatinine, urea, cystatin C, and spot urine albumin levels remained unchanged. The change in estimated glomerular filtration rates (−3.9±10.3 mL/minute per 1.73 m 2 [95% CI, −7.1 to −0.75]; P =0.02) was within the expected range. There were no cases of renal artery stenosis up to 12-month follow-up. Conclusions: Catheter-based chemical renal denervation with dehydrated alcohol using the Peregrine Catheter seems to safely reduce BP at follow-up of up to 12 months. Further randomized and sham controlled studies are underway to further validate these findings. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02570113.